(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Coronary heart disease, a condition associated with dyslipidemias including hyperlipidemia and low HDL-C levels, has been an increasing problem in the developing world. Conventional treatment for hyperlipidemia often present with unfavourable side effects, leading to the need for development of drugs from natural products. The hypoglycemic and hypocholesterolemic properties of the Jamaican bitter yam have previously been demonstrated however consumption at a high dosage presents with various adverse effects. This study is therefore geared towards the determination of an optimal dosage for the consumption of a proprietary preparation made from this yam species. Hypercholesterolemic mice were fed the preparation at various dosages (4, 2, 1, 0.5%) for 3 weeks after which they were phlebotomized then euthanized. Organs were stored at -80°C until required for analysis. The optimal dosage for supplementation, which resulted in significant decreases in serum cholesterol and oxidative stress without eliciting adverse effects, was found to be 2%. The results from this study points to the need for future in-depth studies involving dietary supplementation at the 2% supplementation level.